Potensi Pelanggaran Prinsip Timeliness dalam ICESCR: Analisis Layanan JKN di Indonesia - Willy Johan; Ragil Barry Prastiyo; Dwi Imroatus Sholikah (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
The persistent problem of long waiting times in Indonesia’s National Health Insurance (JKN) services has raised concerns about the fulfillment of the right to health guaranteed under Article 12 of the International Covenant on Economic, Social and Cultural Rights (ICESCR). Although the AAAQ framework Availability, Accessibility, Acceptability, and Quality does not explicitly mention timeliness, delays in medical services directly affect accessibility and quality. This study aims to examine whether service delays within JKN indicate potential non-compliance with Indonesia’s international human rights obligations. Using a normative legal method supported by targeted case illustrations, this research analyzes the alignment between ICESCR standards and the implementation of JKN policies, particularly regarding disparities in service delivery and prolonged waiting times. The findings show that unequal distribution of health facilities, inconsistent service quality between insured and non-insured patients, and extended queues at primary and referral facilities undermine the substantive elements of accessibility and quality. These conditions may constitute a potential breach of the core obligations outlined in ICESCR, despite the absence of a binding enforcement mechanism. Strengthening facility capacity, improving digital service systems, and ensuring equitable distribution of health personnel are identified as essential measures to ensure timely, non-discriminatory, and rights-based health services.